2008
DOI: 10.1042/bj20080617
|View full text |Cite
|
Sign up to set email alerts
|

Human D-Tyr-tRNATyr deacylase contributes to the resistance of the cell to D-amino acids

Abstract: DTD (D-Tyr-tRNA(Tyr) deacylase) is known to be able to deacylate D-aminoacyl-tRNAs into free D-amino acids and tRNAs and therefore contributes to cellular resistance against D-amino acids in Escherichia coli and yeast. We have found that h-DTD (human DTD) is enriched in the nuclear envelope region of mammalian cells. Treatment of HeLa cells with D-Tyr resulted in nuclear accumulation of tRNA(Tyr). D-Tyr treatment and h-DTD silencing caused tRNA(Tyr) downregulation. Furthermore, inhibition of protein synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…For example, in neuronal tissues, D-serine and D-aspartate along with glycine are abundant and act as neurotransmitters/neuromodulators (Hashimoto and Oka, 1997; Snyder and Kim, 2000). In such instances, especially in neuronal tissues, DTD’s function and its corresponding up-regulation (Zheng et al, 2009) suggest an all-pervasive requirement of this protein from a primordial domain involved in perpetuation of homochirality to current-day proofreader in physiological context. It has been established that even a mild compromise in AlaRS editing for Ser-tRNA Ala causes severe pathological conditions, such as neurodegeneration and cardiomyopathy in mouse (Lee et al, 2006; Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in neuronal tissues, D-serine and D-aspartate along with glycine are abundant and act as neurotransmitters/neuromodulators (Hashimoto and Oka, 1997; Snyder and Kim, 2000). In such instances, especially in neuronal tissues, DTD’s function and its corresponding up-regulation (Zheng et al, 2009) suggest an all-pervasive requirement of this protein from a primordial domain involved in perpetuation of homochirality to current-day proofreader in physiological context. It has been established that even a mild compromise in AlaRS editing for Ser-tRNA Ala causes severe pathological conditions, such as neurodegeneration and cardiomyopathy in mouse (Lee et al, 2006; Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the homology between the DUE-B and aminoacyl-tRNA deacylating enzymes, it is formally possible that the inhibition of replication by DUE-B siRNA could arise indirectly through effects on protein synthesis. However, DUE-B siRNA knockdown did not affect tRNA Tyr aminoacylation or [ 3 H]leucine incorporation in HeLa cells (63), suggesting that protein synthesis is not the point at which DUE-B siRNA inhibits cell cycle progress. Nevertheless, the present results cannot distinguish between a decrease in the chromatin loading of RPA and that of Cdc45 due to a direct inhibition of pre-IC formation by DUE-B knockdown or due to an indirect effect through the inhibition of S-phase Cdk activity by elevated p21 protein levels.…”
Section: Due-b Andmentioning
confidence: 99%
“…This clustering represents constant physiological intra-group states, and the grouping in the score plots indicated that the bioavailability and biological utilization of C-AAs vary widely between different milk origins. The enzymes, involved in D-AA synthesis and metabolism include D-AA oxidases, deacylases, dehydrogenases, epimerases, proteases, and racemases, the activities of which may determine the DLAArs of the different milk origins23738394041424344.…”
Section: Resultsmentioning
confidence: 99%